Analisis Penggunaan Jenis Kalimat Dilihat dari Bentuk Sintaksis pada Teks Negosiasi dalam Buku Ajar Bahasa Indonesia Kelas X SMA Kurikulum Merdeka - Ain Nina Nur Fahonah; Aprilia Maharani; Naura Putri; Hidayatul Afifah; Asep Purwo Yudi Utomo; Dwi Setiyawan (Student Research Journal, 2023)
The purpose of this study was to identify the types of sentences seen in the syntactical forms of negotiating texts in Class X SMA Indonesian Textbooks. We conducted this research because it is closely related to learning Indonesian. In this article, we discuss grouping sentences based on type categories from the point of view of syntax, description, and examples of the types of sentences in negotiating texts. We chose an analysis of the types of sentences from the negotiating text so that readers can gain new knowledge and deepen this material more deeply. The type of approach that we use in this study is a qualitative, descriptive approach using note-taking techniques. After we did an analysis of the negotiating text in the Indonesian Language Textbook Class X SMA Merdeka Curriculum, we found that there are four types of sentences in the negotiating text: declarative sentences, imperative sentences, interrogative sentences, and interjective sentences. This research has two benefits, namely theoretical and practical. Theoretically, the results of this study can contribute ideas to writers and reviewers of negotiating texts by helping them understand the types of sentences that are often used in the text. Writers and text reviewers can use the results of this research as a reference to identify and analyze the types of sentences used in negotiating texts, so as to enrich their theoretical understanding of the types of sentences in the context of negotiations. Practically, this research can be useful for researchers and students, especially college students, because it provides insight regarding the use of different types of sentences, especially in negotiating texts.